A study on two-sided matching game of virtual business partners based on heterogeneous multi-attribute preferences and subject's psychological behavior - Xiao, Hanjie (Soft computing (Berlin, Germany), 2023)
Partner selection and matching is a key part of virtual enterprise formation, which directly affects the growth and development of virtual enterprises. The selection and matching of virtual enterprise partners can be regarded as multi-attribute two-sided matching problem. This paper considers the current situation of attribute preferences in the mutual evaluation process of virtual partner selection, introduces a heterogeneous multi-attribute preference evaluation language system, analyzes the psychological behavior characteristics of both subjects in the decision-making process of selection and matching, gives the strategies and conditions of bilateral matching of virtual enterprise partners, and realizes an effective matching with balanced satisfaction of both virtual enterprise partners.